Device Design of Ankle Joint Stretching System Controlled by the Healthy Side Ankle Joint Movement for Self-Rehabilitation - Toda, Hideki; Kawamoto, Hiroaki (Journal of robotics and mechatronics, 2023)
An ankle joint stretching device controlled by healthy-side ankle movements was developed for self-rehabilitation. Physical therapists treat their patients to prevent a subject ankle joint’s contracture and improve their walking function. However, sufficient rehabilitation therapy cannot be performed because of the labor demands of ankle joint rehabilitation. There has long been a demand for a self-rehabilitation system to reduce the amount of labor required, with the rehabilitation system operated by a physical therapist using a machine. Self-rehabilitation has not yet been realized. By stretching the affected ankle through the movement of the ankle on the healthy side, a self-rehabilitation device that can be used according to the will of the patient can be developed. An experiment confirmed that the device can realize affected-side ankle joint stretching by moving a foot plate connected to a linear actuator using the angle of the healthy-side ankle joint as a trigger. Ankle joint rotation angles of the affected and healthy sides were measured using two acceleration sensors. Compared with the previously used button-push-type control, healthy-side control can realize a smooth and stable affected-side sole-pushing procedure. The proposed system, which does not require operation by a physical therapist during treatment, makes self-rehabilitation of the ankle joint possible.